Variation within the host country: How do complementary sub-national levels affect subsidiary discretion on vocational training policies within multinationals?. (April 2015) - Dekocker, Vickie
This paper adapts a cross-comparative case study analysis to investigate how complementary sub-national levels affect subsidiary discretion on vocational training policies in multinationals' subsidiaries in Belgium. The paper addresses three levels: the regional government, the sector, and the web of inter-firm relations. Using case studies of four multinationals with three subsidiaries operating in Belgium, the paper concludes that a high level of subsidiary discretion is found when several sub-national policies are supportive of companies' intended training policies. In other words, if only one level instigates training initiatives or if these initiatives do not fit with the multinationals' training aims, no subsidiary discretion is observed. Furthermore, the paper shows that national surveys on employment practices in multinational companies would benefit from integrating these sub-national levels. Based on the effects of the sub-national levels on discretion, as found in our paper, we expect the sub-national levels to mediate or reinforce the home and host country effect.